Ответы и объяснения

2011-05-15T01:27:28+04:00

Решение

1) x(x+3)^2-(x+2)(x^2-2x+4)-2(x-2)(3x+2)=

    =x(x^2+6x+9)-(x^3-2x^2+4x+2x^2-4x+8)-(2x-4)(3x+2)=

    =x^3+6x^2+9x-x^3+2x^2+4x-2x^2+4x-8-(2x-4)(3x+2)=

    =8x^2+9x-4x-2x^2+4x-8-(6x^2+4x-12x-8)=

    =6x^2+5x+4x-8-6x^2-4x+12x+8=17x

2) (x-1)(x+1)(x^2+1)(x^8+x^4+1)=(x^2-1)(x^2+1)(x^8+x^4+1)=

    =(x^4-1)(x^8+x^4+1)=x^1^2+x^8+x^4-x^8-x^4-1=x^1^2-1

3) (a+b)^2*(a^2-ab+b^2)^2=(a+b)(a+b)(a^2-ab+b^2)(a^2-ab+b^2)=

    =(a+b)(a^3+b^3)(a^2-ab+b^2)=(a^4+ab^3+a^3b+b^4)(a^2-ab+b^2)=

    =a^6-a^5b+a^4b^2+a^3b^3-a^2b^4+ab^5+a^5b-a^4b^2+a^3b^3+a^2b^4-ab^5+b^6=

    =a^6+a^3b^3-a^2b^4+ab^5+a^3b^3+a^2b^4-ab^5+b^6=a^6+2a^3b^3+b^6